How Does AI Improve Emergency Department Triage? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
The emergency department (ED) is a critical component of the healthcare system, but it frequently faces challenges such as overcrowding, long wait times, and...
Keywords: AI in Emergency Medicine; Improve; Emergency; Department; Artificial Intelligence; Machine Learning; Healthcare